Screening and Optimization of Cellulase Production of Bacillus subtilis TD6 Isolated from Takifugu rubripes Fish - Andriani, Dian; Park, Don Hee (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2010)
Cellulase enzymes have attracted considerable attention in recent years due to their great biotechnological and industrial potential. Cellulase enzymes provide a key opportunity for achieving tremendous benefits of biomass utilization through the bioconversion of the most abundant cellulosic material into the simplest carbohydrate monomer, glucose. Nowadays, the sources of cellulase-producing bacteria have been broadened into thepresence of symbiotic bacteria in herbivorous animal and also from marine. Takifugu rubripes or known as puffer fish is a unique poisonous vertebrate but nevertheless is considered a delicacy in Korea. The diet of the puffer fish includes mostly algae. This dietary habit considers Puffer fish as host of cellulase-producing bacteria, especialy on its gut. In the present study an attempt has been made to search for the cellulolytic bacteria in the gut of Takifugu rubripes. Fifty five microorganisms have been isolated using 1% (w/v) Carboxymethyl cellulose (CMC) as substante Congo red dye test and DNS method were then used for screening the extracellular celuase activity of the strains. Among them, TD6 strain has shown the highest performance in term of cellulose activity. In order to evaluate the optimum culture condition of the isolate TD6 for cellulase production, the strain was grown at various temperatures, pH, carbon sources, and nitrogen sources. Under optimum condition, the maximum specific activity of 2.13 U/mg protein was achieved after growth the strain with 1.5% CMC at 45ºC PH 6 for 3 days, respectively Based on 16S rRNA gene analysis it is proposed that the strain was identified asBacillus subtilis.